Principles of environmental economics : economics, ecology and public policy - Hussen, Ahmed M. (Routledge, 2000)
This book is divided into eight parts: The "Preanalytic" Vision of Natural Resources: The Standard Economic Perspective; Market, Efficiency, Technology and Alternative Economic Indicators of Natural Resource Scarcity; Ecology: The Economics of Nature; Fundamentals of the Economics of Environmental Resources; The Perennial Debates on the Biophysical Limitations to Economic Growth; The Economics of Environmental Resources: Public Policies and Cost-Benefit Estimations of Environmental Damage; Basic Elements of the Economic theories of Renewable and Nonrenewable Resources; and Resources Scarcity, Population, Poverty and the Environment.